Effect of Biochar and Wood Distillate on Vegeto-Productive Performances of Tomato (Solanum lycopersicum L.) Plants, var. Solarino, Grown in Soilless Conditions - Anna Agosti; Samreen Nazeer; Lorenzo Del Vecchio; Leandra Leto; Andrea Di Fazio; Jasmine Hadj-Saadoun; Alessia Levante; Massimiliano Rinaldi; Rohini Dhenge; Camilla Lazzi; Martina Cirlini; Benedetta Chiancone (Agronomy)
Nowadays, tomato, a commercially important crop, is increasingly cultivated in a soilless cultivation system to counteract climate change. Normally, this system uses cocopeat as a substrate, but its high cost and environmental impact have led to growing interest in alternatives like biochar (BC). In addition, biostimulants, such as wood distillate (WD), a pyrolysis by-product, are increasingly being used to improve fruit yield and quality. BC was used to partially replace (2% and 5%) cocopeat in growth bags for soilless tomato cultivation. Moreover, WD (3 mL/L) was distributed in the substrate every two weeks. The effect of BC and WD on tomato plant growth, fruit quality, and substrate microbial community was investigated. The integration of BC and WD into a soilless growing system for tomato cultivation can improve the fruit quality and influence the microbial activity of the substrate. Replacing part of the cocopeat in the substrate with BC and using an agri-waste-derived biostimulant represent a step forward in making agriculture more sustainable.